Hundred Pediatric Cases Treated for Chiari Type II Malformation with Hydrocephalus and Myelomeningocele - Encarnacion, Daniel; Chmutin, Gennady; Chaurasia, Bipin; Bozkurt, Ismail (Asian Journal of Neurosurgery, 2023)
Background Chiari malformation type II (CM-II) may not always present as an asymptomatic disorder but prove to be difficult in managing. This is especially true for neonates who show the worst prognosis. There is confounding data over whether shunting or craniocervical junction (CVJ) decompression should be employed. This retrospective analysis summarizes the results of 100 patients diagnosed and treated for CM-II along with hydrocephalus and myelomeningocele.Methods We reviewed all the children who were diagnosed and surgically treated for CM-II at the Moscow Regional Hospital. Surgical timing was decided on the clinical conditions of each patient. Urgent surgery in the more compromised patients (usually infants) and elective surgery for patients with less severe conditions was performed. All patients first underwent CVJ decompression.Results The retrospective review yielded 100 patients operated on for CM-II with concomitant hydrocephalus and myelomeningocele. The average herniation was 11.2 ± 5.1 mm. However, herniation level did not correlate with clinical findings. Concomitant syringomyelia was observed in 60% of patients. More severe spinal deformity was observed in patients with widespread syringomyelia (p = 0.04). In children of the younger age group, cerebellar symptoms and bulbar disorders were more frequently observed (p = 0.03), and cephalic syndrome was noted much less frequently (p = 0.005). The severity of scoliotic deformity correlated with the prevalence of syringomyelia (p = 0.03). Satisfactory results were significantly more often observed in patients of the older age group (p = 0.02). Patients with unsatisfactory results at the time of treatment were significantly younger (p = 0.02).Conclusion If CM-II is asymptomatic, then no specific treatment is prescribed. If the patient develops pain in the occiput and neck, then pain relievers are prescribed. If a patient has neurological disorders or concomitant syringomyelia, hydrocephalus or myelomeningocele, surgical intervention is indicated. The operation is also performed if the pain syndrome cannot be overcome within the framework of conservative therapy.
Keywords: Chiari II malformation; craniocervical junction decompression; myelomeningocele; spina bifida; syringomyelia